Seeds - Austen, Elizabeth (Huntington Beach, CA : Teacher Created Materials, 2015)
"It is time to learn how seeds grow."-- Provided by publisher.
Plenty of plants! -- Growing up green -- Time to eat! -- Plant families -- Around the world -- Let's do science!
Includes index
K to grade 3
Keywords: Seeds -- Juvenile literature